Snazzy cat capers - Kent, Deanna (Kent, Deanna. Snazzy cat capers, 2018)
Life is short. Diamonds are fur-ever. Internationally famous cat burglar Ophelia von Hairball V adores jewels--the only thing she loves more is a challenge. She's never met a safe she couldn't crack. Now the Furry Feline Burglary Institute (FFBI) offers her the ultimate caper: steal the giant Himalayan diamond and win their top award! There's a catch! The FFBI sends an enthusiastic inventor to help Ophelia...but this cat works alone, and Oscar Fishgerald Gold smells fishy. Can the smartest, stealthiest, and snazziest of cats learn to work with a fintastic sidekick and prove she's still the world's most purr-fect burglar?--